What supports mothers of very preterm babies to start and continue breast milk feeding neonatal units? A qualitative COM-B analysis of mothers’ experiences - Jenny McLeish; Annie Aloysius; Chris Gale; Maria A. Quigley; Jennifer J. Kurinczuk; Fiona Alderdice (BMC Pregnancy and Childbirth)
Abstract Background It is challenging for mothers who give birth very preterm to produce sufficient breast milk by expressing for weeks before their baby is able to feed from the breast, and then to transition from tube feeding to breastfeeding. Lactation is most successful when stimulated shortly after birth, established within 72 h, and maintained by expressing 6–8 times a day. This study explored mothers’ experiences of how breast milk feeding and breastfeeding for very preterm babies can be supported by staff and the facilities of a neonatal unit. Methods Twenty-three mothers of very preterm babies were interviewed, from four neonatal units in England with high or low rates of breast milk feeding at discharge. Interviews were analysed using the COM-B framework to consider how mothers’ behaviour (breast milk feeding and breastfeeding) is affected by capability, opportunity and motivation. Results Mothers’ motivation in the traumatic situation of very preterm birth was strongly affected by information from staff about the benefits of breast milk for their baby, the importance of early and frequent expressing, and how to assess the effectiveness of direct breastfeeding. It was maintained through positive feedback about their efforts which built their confidence, and reassurance about what is ‘normal’ growth when a baby begins direct breastfeeding. Motivation needed to be supported by opportunity, including access to equipment for expressing and facilities to stay near the neonatal unit, and also by capability, which required proactive and skilled information and support from staff. Specialist support and facilities varied between units, and some mothers were not given necessary information or had their motivation undermined by staff comments. Conclusions Interventions to increase breast milk feeding and breastfeeding for very preterm babies should address mothers’ motivation, capability and opportunity, aiming for systematic elimination of obstacles. Mothers value personalised and skilled specialist support, but also need other staff to be able to give consistent information and affirmation focused on their efforts rather than their success, with a trauma-informed approach. Investing in rooming-in facilities that minimise the separation of mothers and babies is likely to overcome a key obstacle.